Withdrawn: Parenteral Nutrition in a GLUT1DS Patient Following Classic Ketogenic Diet: Ideal versus Real‐World Management in an Acute Surgical Setting. Issue 8 (20th May 2022) - Varesio, Costanza; Ferraris, Cinzia; Gentilino, Valerio; Brena, Mario Leo; Farris, Giorgio; Guglielmetti, Monica; Marazzi, Claudia; Pasca, Ludovica
Abstract : Withdrawal: C Varesio et al., Parenteral Nutrition in a GLUT1DS Patient Following Classic Ketogenic Diet: Ideal versus Real‐World Management in an Acute Surgical Setting, Journal of Parenteral and Enteral Nutrition 2022 (https://doi.org/10.1002/jpen.2361 ). The above article, published online on March 1st, 2022 in Wiley Online Library (wileyonlinelibrary.com ), has been withdrawn by agreement between the journal Editor‐in‐Chief, Kelly A. Tappenden, PhD, RD, FASPEN, and Wiley Periodicals LLC. The article was published as the result of an administrative error.